1982
DOI: 10.1007/bf02010449
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electron Transport System (ETS) activity in soil

Abstract: Electron transport system (ETS) activity was measured in amended and nonamended soil by measuring the reduction of 2-(p-iodophenyl)-3-(p-nitrophenyl)-5-phenyl tetrazolium chloride (INT) to iodonitrotetrazolium formazan (INT-formazan), which can be easily extracted with methanol without interference from other compounds found in soil. A high correlation between ETS activity and oxygen consumption was observed. This technique allows rapid quantitative measurements of microbial ETS activity in soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(58 citation statements)
references
References 6 publications
1
55
0
2
Order By: Relevance
“…INT reduction assays similar to the one used here have been suggested as a quantitative measure of metabolic activity in a variety of systems, including marine sediments (Houri-Davignon et al 1989), estuarine sediments (Trevors 1984a), freshwater sediments (Trevors 1984b), soils (Trevors et al 1982, Trevors 1984c, von Mersi and Schinner 1991, Friedel et al 1994, Garcia et al 1994, river biofilms (Blenkinsopp and Lock 1990), and peat (Gammelgaard et al 1992). In many of these studies, INT reduction was correlated with some independent measure of metabolic activity, most commonly 02 consumption or CO2 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…INT reduction assays similar to the one used here have been suggested as a quantitative measure of metabolic activity in a variety of systems, including marine sediments (Houri-Davignon et al 1989), estuarine sediments (Trevors 1984a), freshwater sediments (Trevors 1984b), soils (Trevors et al 1982, Trevors 1984c, von Mersi and Schinner 1991, Friedel et al 1994, Garcia et al 1994, river biofilms (Blenkinsopp and Lock 1990), and peat (Gammelgaard et al 1992). In many of these studies, INT reduction was correlated with some independent measure of metabolic activity, most commonly 02 consumption or CO2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Trevors et al (1982) and Houri-Davignon et al (1989) reported slopes of 0.0155 and 0.0377, respectively. Despite significant two-way interactions in the ANOVA (Table 1), an a posteriori comparison of all means revealed treatment effects (Figure 1).…”
Section: Formalin Int and Extractant Effects On Int Reduction Measumentioning
confidence: 99%
“…Arylsulfatase enzymes catalyze the hydrolysis of sulfate esters resulting in the release of SO 4 2− , being important to S cycling processes in wetland soils (Tabatabai and Bremner 1970). Finally, dehydrogenase enzyme activity is used as a measurement of the overall biological activity in soils (Trevors et al 1982).…”
Section: Extracellular Enzyme Activities and Nutrient Availability Inmentioning
confidence: 99%
“…Large amount of information about biological characteristic of the soil is obtained by the determination of DHA in soil (Wolinska and Stepniewska, 2012). Dehydrogenase enzyme is often used as a measure of soil microbial activity and gives account of any disruption caused by pesticides, trace elements or management practices to the soil (Chendrayan et al, 1979;Trevors et al, 1982;McCarthy et al, 1994). Soil DHA is considered to exist in soils as integral parts of intact cells (Taylor et al, 2002).…”
Section: Microbiological Indicesmentioning
confidence: 99%